2007
DOI: 10.1163/22941932-90001654
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Primary Lenticels of olea Europaea and Cercis Siliquastrum During The Year

Abstract: The structure of primary lenticels of the Mediterranean evergreen Olea europaea and the winter deciduous species Cercis siliquastrum was investigated during the year using scanning electron, conventional brightfield and epi-fluorescence microscopy. It was revealed that lenticels of O. europaea do not undergo significant structural changes over this time period. The filling tissue of O. europaea lenticels consists of fully-suberized cells that form small intercellular spaces. The air-exposed filling cells are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Lenticels permit gas exchange through the otherwise impervious periderm. For Olea europaea and Cercis siliquastrum, the parenchyma cells beneath the lenticels showed a brighter red auto-fluorescence than those elsewhere [ 64 ], similar to that described for stomata in the young eucalypt branchlets. It has also been suggested that lenticels may also permit more light into the stem than the general periderm but this was not substantiated in a study of 10 species that examined one-year-old twigs [ 65 ].…”
Section: Discussionsupporting
confidence: 72%
“…Lenticels permit gas exchange through the otherwise impervious periderm. For Olea europaea and Cercis siliquastrum, the parenchyma cells beneath the lenticels showed a brighter red auto-fluorescence than those elsewhere [ 64 ], similar to that described for stomata in the young eucalypt branchlets. It has also been suggested that lenticels may also permit more light into the stem than the general periderm but this was not substantiated in a study of 10 species that examined one-year-old twigs [ 65 ].…”
Section: Discussionsupporting
confidence: 72%
“…Lenticel presence, number, type, degree of opening, development stage and area vary between tree species (Langenfeld‐Heyser, ; Kalachanis & Psaras, ). Moreover, the development stage of a tree species (Lendzian, ; Kalachanis & Psaras, ), which commonly is affected by external factors and environmental conditions, also impacts the formation of lenticels (Kuo‐Huang & Hung, ). Any change in stem lenticel density may influence development of stem and root aerenchyma tissues, and thus potentially alter rates of CH 4 transport.…”
Section: Discussionmentioning
confidence: 99%
“…While our study demonstrates a strong positive relationship between stem lenticel density and tree‐mediated CH 4 emissions in A. glutinosa , further work is required to determine whether such a relationship is common in other tree species. Lenticel presence, number, type, degree of opening, development stage and area vary between tree species (Langenfeld‐Heyser, ; Kalachanis & Psaras, ). Moreover, the development stage of a tree species (Lendzian, ; Kalachanis & Psaras, ), which commonly is affected by external factors and environmental conditions, also impacts the formation of lenticels (Kuo‐Huang & Hung, ).…”
Section: Discussionmentioning
confidence: 99%
“…We looked for orthologues of genes that are involved in stomatal development because it is believed that stomata are the founder structures for lenticular channels (Kalachanis and Psaras, 2007). We screened the Q. suber phellogen transcriptome database using the Arabidopsis bHLH transcription factors encoded by the FAMA, SPEECHLESS, and MUTE genes; and Arabidopsis homeodomain-leucine zipper IV proteins encoded by MERISTEM LAYER 1 (ML1) and HOMEODOMAIN GLABROUS2 (HDG2) genes.…”
Section: Analysis Of Putative Genes Involved In Lenticel Developmentmentioning
confidence: 99%